Neoliberalismo e financeirização da educação superior no Brasil : uma análise do posicionamento, da perspectiva e enfoque epistemetodológico nas teses em educação (2013-2022) - Juliani, Marcio Pedroso (2025)
This study examines how categories related to financialization, neoliberalism, commodification and expansion of Higher Education were treated in doctoral theses in the field of Education in Brazil in the time frame from 2013 to 2022. The scope of this study is to identify and analyze the positions, perspectives and epistemological approaches present in these academic productions. Based on a meta-research involving 30 theses selected from the CAPES Theses and Dissertations Catalog, the analysis reveals a predominance of critical approaches, mainly Marxist-based, which point to the transformation of Education into a commercial good and the effects of neoliberal policies on the education sector. The research uses the Approach to Epistemologies of Educational Policy (EEPE) and combines qualitative methods, content analyses and the construction of a network of theses and cited references. The findings indicate theoretical weaknesses in some theses, but also mark important advances in terms of analytical coherence and social commitment. The construction of the network elaborated with the referenced authors indicates that the researchers have sought to ventilate the theoretical framework, opening space for new discussions and results, but without neglecting the classical theoretical basis in their investigations. This work offers a significant contribution to the field of Educational Policy by suggesting an analytical model that unites theory and method in a harmonious way, in addition to emphasizing the need to improve epistemic formation in postgraduate studies as a step towards strengthening the production of critical and liberating knowledge.